2014
DOI: 10.1097/gox.0000000000000065
|View full text |Cite
|
Sign up to set email alerts
|

Silicone Breast Implants Can Save Lives

Abstract: Summary:The authors present a case in which a patient sustained 2 shotgun wounds at close range, resulting in a ruptured silicone breast implant and no other injuries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 2 publications
0
5
0
Order By: Relevance
“…In contrast, Rosen and colleagues published a case report of a close‐range shotgun injury to the chest, in which the shotgun pellets were stopped by a subpectoral silicone implant. Pellets were embedded within the implant and did not penetrate the intrathoracic cavity . Unlike the reports from Pramod, Fraga‐Dolli, and Pereira, in which implant rupture was reported as collateral damage after a gunshot wound, Rosen describes a case in which a silicone implant was specifically protective against intrathoracic injury.…”
Section: Discussionmentioning
confidence: 90%
“…In contrast, Rosen and colleagues published a case report of a close‐range shotgun injury to the chest, in which the shotgun pellets were stopped by a subpectoral silicone implant. Pellets were embedded within the implant and did not penetrate the intrathoracic cavity . Unlike the reports from Pramod, Fraga‐Dolli, and Pereira, in which implant rupture was reported as collateral damage after a gunshot wound, Rosen describes a case in which a silicone implant was specifically protective against intrathoracic injury.…”
Section: Discussionmentioning
confidence: 90%
“…This work builds upon an increasing body of research showing unexpected and direct benefits of breast implants in traumatic injury. Breast implants have been correlated with injury prevention or injury minimization in firearms injuries 8,[10][11][12][13] as well as animal attacks. 9 An experimental model of gunshot injuries previously published demonstrated that the presence of a breast implant decreased soft tissue penetration by 20.6%, supporting the plausibility of implant-mediated protection.…”
Section: Positive Impact Of Breast Implantsmentioning
confidence: 99%
“…Breast implants can minimize human injury in penetrating trauma, 8–13 which is fortunately rare. Blunt traumatic injury is more common.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…8,9 Rosen et al were the first to show that breast implants can save a life with a case of a silicone implant stopping shotgun pellet. 10 Pannucci et al were the first to detail a report of a saline breast implant saving a patient’s life due to effects on bullet velocity. 11 Here, we report the first case in the literature of a 30-year-old female patient with silicone breast implants altering bullet trajectory and thereby saving her life.…”
Section: Introductionmentioning
confidence: 99%